PENINGKATAN KETERAMPILAN MENULIS DESKRIPSI MAHASISWA DENGAN TEKNIK OBYEK LANGSUNG MELALUI MODEL PEMBELAJARAN “RISMA” - Budi Riwayati, Yuli; Danu Rusmawati, Retno (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
This study aimed to describe the improvement of students’ writing skills technique majoring in Indonesian language education and literature class of 2007 A Unipa Surabaya through direct object "RISMA" learning model. This research is a classroom action research. The data were collected by using test and non-test. The test data was taken from the students' writing skills technique test implementing direct object "RISMA" learning model, while non-test data is taken from a student observation sheet. These data were analyzed with quantitative and qualitative techniques. Quantitative techniques are used to analyze data test, while the qualitative techniques used to analyze the non-test data. The results of quantitative descriptive analysis states that in the first cycle the average value of students increased by 73.83, while in the second cycle an average increase of 85.18.